2005
DOI: 10.1002/mrc.1646
|View full text |Cite
|
Sign up to set email alerts
|

ESR spin‐label study of poly(styrene‐co‐methacrylic acid)/poly(ε‐caprolactone) semi‐interpenetrating polymer networks with controlled hydrogen‐bond interactions

Abstract: The morphology and miscibility of semi-interpenetrating polymer networks (semi-IPN) prepared with poly(styrene-co-methacrylic acid) [P(S-co-MAA)] of different carboxylic acid contents and poly(epsilon-caprolactone) (PCL) have been studied by ESR spin-label method. The ESR spectra of spin-labeled PCL showed one motional component at any specific temperature. It indicated that the spin-labeled molecules were located in one type of environment. The coexistence of two motional components in the ESR spectra of all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The miscibility can be improved by increasing the carboxylic acid content, which could enhance the hydrogenbonding interactions between the ester groups of PCL and carboxylic acid groups in P(S-co-MAA). It was also found that the microphase separation became more remarkable with increasing intracomponent crosslinking of the SIPNs [82].…”
Section: Semi-interpenetrating Network (Sipns)mentioning
confidence: 82%
“…The miscibility can be improved by increasing the carboxylic acid content, which could enhance the hydrogenbonding interactions between the ester groups of PCL and carboxylic acid groups in P(S-co-MAA). It was also found that the microphase separation became more remarkable with increasing intracomponent crosslinking of the SIPNs [82].…”
Section: Semi-interpenetrating Network (Sipns)mentioning
confidence: 82%